Pengaruh E-Module Sistem Pernapasan Berbasis Praktikum terhadap Hasil Belajar untuk Menunjang SDGs 3 Siswa Kelas XI SMA Negeri 13 Samarinda - Nofalia, Adinda Devi; Nasution, Ruqoyyah; Rambitan, Vandalita Maria Magdalena; Jailani, Jailani; Makkadafi, Suparno Putera (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Technological progress requires innovation in all components of education, one of which is by integrating the Sustainable Development Goals (SDGs) into learning through practicum-based breathing system e-modules. This study aims to analyze the influence of practicum-based respiratory system e-modules on the learning outcomes of grade XI students of SMA Negeri 13 Samarinda in the cognitive, affective, and psychomotor domains in supporting the achievement of SDGs 3. The research method used a quasi experiment type of non-equivalent control group with two subjects (30 students each), one class as an experiment and one class as a control. Instruments include cognitive tests (pretest–posttest) as well as affective and psychomotor observations. Cognitive data analysis used an independent t-test, while affective and psychomotor were analyzed descriptively and converted to qualitative categories. The results showed significant differences in cognitive learning outcomes (sig. 0.000 < 0.05). The affective learning outcomes of both classes were in the good category, with the experimental class showing a higher score of 78.89, while the control class was 74.11. The psychomotor learning outcomes of the experimental class were in the skilled category with an average of 75.09, while the control class was quite skilled with an average of 69.17. Therefore, it is concluded that practicum-based e-modules are effective in improving learning outcomes while fostering health and environmental awareness in accordance with SDGs 3.